Post-translational activation of the C-terminus of polypeptides for the synthesis of peptide thioesters and peptide thioester surrogates - Liu, Yanbo; Kajihara, Yasuhiro; Okamoto, Ryo (Frontiers in Chemistry, 2024)
Semisynthesis using recombinant polypeptides is a powerful approach for the synthesis of proteins having a variety of modifications. Peptide-thioesters, of which peptide C-terminus is activated by thioester, are utilized for coupling peptide building blocks. Biological methods employing intein have been a center for the C-terminal thioesterification of recombinant polypeptides. Chemical activation has emerged as an alternative methodology for synthesizing peptide-thioesters from recombinant polypeptides. Chemical reactions are compatible with various solutions containing organic solvents, chaotropic reagents, or detergents, generally incompatible with biomolecules such as intein. Despite the potential utility of chemical activation, available methods remain limited. Herein, this article introduces the methods for the chemical activation of peptide C-terminus, applied to the chemical synthesis of proteins. By showcasing these methodologies, we aim to accelerate the advancement of new chemical reactions and methodologies and broaden the frontiers for the chemical synthesis of proteins.